2018
DOI: 10.1097/gox.0000000000001841
|View full text |Cite
|
Sign up to set email alerts
|

Contact Dermatitis Caused by Dermabond Advanced Use

Abstract: Background:Dermabond Advanced (DBA) has been widely used globally; however, severe contact dermatitis (CD) can be a serious adverse effect of DBA use. In this study, we investigated the characterization and incidence rate of CD after using DBA and the safe use of DBA.Methods:One hundred consecutive patients who underwent skin closure with DBA were investigated. All patients were women undergoing breast reconstruction. DBA was applied to their trunk and limbs following reconstruction.Results:Seven patients (7%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 16 publications
2
10
2
Order By: Relevance
“…In this study of liquid adhesive-related contact dermatitis, 2.8% of patients developed contact dermatitis. Compared with the incidence (29/6008, 0.5%) reported by Chalmers et al, [ 11 ] the incidence in our study was higher, whereas it was lower than the incidence reported by Nakagawa et al [ 12 ] (7/100, 7%). Chalmers et al [ 11 ] used Dermabond Prineo skin closure system (Ethicon Inc., NJ) containing 2-octyl cyanoacrylate and Nakagawa et al [ 12 ] used Dermabond Advanced topical skin adhesive (Ethicon Inc., NJ) containing 2-octyl cyanoacrylate, each.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…In this study of liquid adhesive-related contact dermatitis, 2.8% of patients developed contact dermatitis. Compared with the incidence (29/6008, 0.5%) reported by Chalmers et al, [ 11 ] the incidence in our study was higher, whereas it was lower than the incidence reported by Nakagawa et al [ 12 ] (7/100, 7%). Chalmers et al [ 11 ] used Dermabond Prineo skin closure system (Ethicon Inc., NJ) containing 2-octyl cyanoacrylate and Nakagawa et al [ 12 ] used Dermabond Advanced topical skin adhesive (Ethicon Inc., NJ) containing 2-octyl cyanoacrylate, each.…”
Section: Discussioncontrasting
confidence: 87%
“…Skin adhesive-related contact dermatitis results from a type IV hypersensitivity reaction, which is a delayed reaction to a substance to which the patient was previously exposed. [ 12 ] It often presents with pruritis, eczema, oedema, and blisters, usually beginning 1 to 2 weeks after exposure. Allergic contact dermatitis is diagnosed by identifying a typical combination of skin lesion, previous exposure to the antigen, consistent patch and blood test results and tissue examination findings, and appropriate response to the dermatitis treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in joint arthroplasty surgery, Michalowitz et al 23 reported an incidence of 1.8% in 281 patients and Durando et al 24 reported 1.7% in 912 patients. Interestingly, Nakagawa et al 25 reported a 7.0% incidence of ACD in 100 patients who underwent breast reconstruction surgery. Except for Nakagawa et al, our incidence of 2.7% is somewhat higher than the previously reported incidence, but studies to date alone cannot clarify whether this is due to the difference in application site or patient demographics.…”
Section: Discussionmentioning
confidence: 99%
“…); d) performance in wet environments, such as physiological fluids; and e) degradation without impeding healing or inflammation, while also maintaining adhesive strength long enough to facilitate native wound closure [23]. Many of the proposed adhesives utilize crosslinking initiators that may be toxic or unsuited for specific applications (i.e., photoinitiation [24], or aldehyde crosslinking, which may elicit an immune response [25]), and weaken rapidly in liquids [26]. For example, tissues repositioned with acrylate-based adhesives may heal better than with sutures [27], yet acrylate glues can elicit a fibrotic response, and weaken under wet-field conditions [21].…”
Section: Introductionmentioning
confidence: 99%